Mouse gastric tumor models with prostaglandin E(2 )pathway activation show similar gene expression profiles to intestinal-type human gastric cancer - Itadani, Hiraku (BioMed Central, 2009)
BACKGROUND: Gastric cancers are generally classified into better differentiated intestinal-type tumor and poorly differentiated diffuse-type one according to Lauren's histological categorization. Although induction of prostaglandin E(2 )pathway promotes gastric tumors in mice in cooperation with deregulated Wnt or BMP signalings, it has remained unresolved whether the gastric tumor mouse models recapitulate either of human gastric cancer type. This study assessed the similarity in expression profiling between gastric tumors of transgenic mice and various tissues of human cancers to find best-fit human tumors for the transgenic mice models. RESULTS: Global expression profiling initially found gastric tumors from COX-2/mPGES-1 (C2mE)-related transgenic mice (K19-C2mE, K19-Wnt1/C2mE, and K19-Nog/C2mE) resembled gastric cancers among the several tissues of human cancers including colon, breast, lung and gastric tumors. Next, classification of the C2mE-related transgenic mice by a gene signature to distinguish human intestinal- and diffuse-type tumors showed C2mE-related transgenic mice were more similar to intestinal-type compared with diffuse one. We finally revealed that induction of Wnt pathway cooperating with the prostaglandin E(2 )pathway in mice (K19-Wnt1/C2mE mice) further reproduce features of human gastric intestinal-type tumors. CONCLUSION: We demonstrated that C2mE-related transgenic mice show significant similarity to intestinal-type gastric cancer when analyzed by global expression profiling. These results suggest that the C2mE-related transgenic mice, especially K19-Wnt1/C2mE mice, serve as a best-fit model to study molecular mechanism underlying the tumorigenesis of human gastric intestinal-type cancers.